(untitled) (Revista Latino-Americana de Enfermagem, 2004)
This experiment aimed to rank nurses' social perception through the magnitude and category estimation methods. Study participants were high school and university students, active and retired professionals in the areas of medicine, psychology, nursing and dentistry. The results showed: (1) the characteristics neat, responsible, clean, careful and efficacious occupied the first positions in terms of nurses' social perception; whereas the characteristics useless, dishonorable, irresponsible and hateful occupied the last positions in the scales obtained by the two direct psychophysical methods, and (2) the non-metric social perception continuum has prosthetic characteristics.